2019
DOI: 10.1111/mec.15116
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of hybridogenetic lineages in Cataglyphis ants

Abstract: In most social Hymenoptera, a diploid egg develops into either a queen or a worker depending on environmental conditions. Hybridogenetic Cataglyphis ants display a bizarre genetic system, where queen‐worker caste determination is primarily determined by genetic factors. In hybridogenetic populations, all workers are F1 hybrids of two distinct lineages, whereas new queens are nearly always pure‐lineage individuals produced by clonal reproduction. The distribution and evolutionary history of these hybridogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
(119 reference statements)
0
15
0
Order By: Relevance
“…Experimental laboratory observations revealed that only a very small proportion of worker‐laid haploid eggs and none of diploid eggs reach adulthood (Leniaud et al, ; Eyer et al, ; A. Kuhn and H. Darras, personal observation). In line with this, across all hybridogenetic Cataglyphis species studied so far, the hundreds of reproductive individuals collected from the field were of pure breeding lineages – no hybrid males or queens (except one; Darras et al, ) have been found, making very unlikely that worker‐laid eggs (if any) achieve their development into viable and fertile hybrid sexuals. Altogether, these results suggest that obligate crossing may have lessened worker fertility, thereby reducing queen‐worker conflict over male and female parentage within colonies.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Experimental laboratory observations revealed that only a very small proportion of worker‐laid haploid eggs and none of diploid eggs reach adulthood (Leniaud et al, ; Eyer et al, ; A. Kuhn and H. Darras, personal observation). In line with this, across all hybridogenetic Cataglyphis species studied so far, the hundreds of reproductive individuals collected from the field were of pure breeding lineages – no hybrid males or queens (except one; Darras et al, ) have been found, making very unlikely that worker‐laid eggs (if any) achieve their development into viable and fertile hybrid sexuals. Altogether, these results suggest that obligate crossing may have lessened worker fertility, thereby reducing queen‐worker conflict over male and female parentage within colonies.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast, in nonhybridogenetic species or populations, workers are produced by sexual reproduction between partners belonging to the same gene pool (random mating). To determine whether or not workers resulted from hybrid matings, we analysed genetic variability among reproductive individuals and determined whether mating patterns were disassortative or random using the genotype webs approach (Darras et al, ). For each species, a Principal Coordinate Analysis (PCoA) based on the genotypes of the reproductives (the mother queens and their inferred male mates) was performed with genalex version 6.502 (Peakall & Smouse, , ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations